Detection of oncogenic viruses in water environments by a Luminex-based multiplex platform for high throughput screening of infectious agents. (15th October 2017) - Di Bonito, P.; Iaconelli, M.; Gheit, T.; Tommasino, M.; Della Libera, S.; Bonadonna, L.; La Rosa, G.
Abstract: Recent studies documented the detection of viruses strongly associated with human cancer in urban sewages and other water environments worldwide. The aim of this study was to estimate the occurrence of human oncogenic viruses in environmental samples (sewage, river, marine, and pool/spa water) using highly sensitive and specific multiplex bead-based assays (Luminex technology). A total of 33 samples were analysed for 140 oncogenic viral agents, including mucosal and cutaneous human papillomaviruses (HPVs), human polyomaviruses (HPyV), human herpesviruses (HHV) and mouse mammary tumour virus (MMTV). Eighty-eight percent of the samples tested positive for at least one viral pathogen and the simultaneous presence of more than one virus was frequent (mean number of positivities/sample = 3.03). A total of 30 different Alpha, Beta and Gamma HPVs were detected, including mucosal and cutaneous types. The high-risk type HPV16 was the most frequently detected virus, identified in 73% of the samples. Of the 12 HPyVs tested, only two (BKPyV and MCPyV) were detected. At least one of these two was present in 48% of the samples. MMTV was detected in 21% of the samples, while herpesviruses - HHV-6 and HHV-1 - were detected in two samples (6%). The present study is the first to provide a comprehensive picture of the occurrence of oncogenic viruses belonging to different families and species in diverse water environments, and the first to successfully use, in environmental samples, a Luminex-based multiplex platform for high throughput screening of infectious agents. Our findings, showing that oncogenic viruses are ubiquitous in water environments, pave the way for future studies on the fate of these pathogens in water environments as well as on their potential for transmission via the waterborne route. Graphical abstract: Image 1 Highlights: A multiplex bead-based assay to detect oncogenic viruses in water. Widespread viral contamination detected in waters. Simultaneous detection of different oncogenic viruses. Human papillomavirus as the most frequently detected virus.